Effect of Addition of Kappaphycus alvarezii on Physicochemical Characteristics and Consumer Acceptance of Fishballs Clarias sp. - Sali, Renzy; Mismawati, Andi; Zuraida, Ita; Diachanty, Seftylia; Pamungkas, Bagus Fajar (Sam Ratulangi University, 2024)
Fish balls containing high protein but low in fiber need to be diversified to increase the nutritional value while reducing the cost of raw materials. Kappaphycus alvarezii seaweed is rich in fiber and the price is relatively cheaper, so it has the potential to be used as raw material for making fish balls. This study aims to determine the physicochemical characteristics and consumer acceptance of catfish meatballs (Clarias sp.) with the addition of K. alvarezii seaweed. The study used a completely randomized design with four treatments, namely the percentage of seaweed substitution for fish meat (w/w) namely 40%, 50%, 60% and 0% (control) with three replications. Parameters observed were proximate composition, whiteness degree, and hedonic test. The addition of seaweed increased the water content, ash, carbohydrates and whiteness value of fish balls but decreased the protein and fat content. Consumers still prefer the formulation of fish balls without the addition of K. alvarezii seaweed, but that is close to consumer preferences with the addition of 40% seaweed.